Sensitization of H2O2-induced TRPM2 activation and subsequent interleukin-8 (CXCL8) production by intracellular Fe2+ in human monocytic U937 cells. (November 2015) - Shimizu, Shunichi; Yonezawa, Ryo; Negoro, Takaharu; Yamamoto, Shinichiro; Numata, Tomohiro; Ishii, Masakazu; Mori, Yasuo; Toda, Takahiro
Abstract: Transient receptor potential melastatin 2 (TRPM2) is an oxidative stress-sensitive Ca 2+ -permeable channel. In monocytes/macrophages, H2 O2 -induced TRPM2 activation causes cell death and/or production of chemokines that aggravate inflammatory diseases. However, relatively high concentrations of H2 O2 are required for activation of TRPM2 channels in vitro. Thus, in the present study, factors that sensitize TRPM2 channels to H2 O2 were identified and subsequent physiological responses were examined in U937 human monocytes. Temperature increase from 30 °C to 37 °C enhanced H2 O2 -induced TRPM2-mediated increase in intracellular free Ca 2+ ([Ca 2+ ]i ) in TRPM2-expressing HEK 293 cells (TRPM2/HEK cells). The H2 O2 -induced TRPM2 activation enhanced by the higher temperature was dramatically sensitized by intracellular Fe 2+ -accumulation following pretreatment with FeSO4 . Thus intracellular Fe 2+ -accumulation sensitizes H2 O2 -induced TRPM2 activation at around body temperature. Moreover, intracellular Fe 2+ -accumulation increased poly(ADP-ribose) levels in nuclei by H2 O2 treatment, and the sensitization of H2 O2 -induced TRPM2 activation were almost completely blocked by poly(ADP-ribose) polymerase inhibitors, suggesting that intracellular Fe 2+ -accumulation enhances H2 O2 -induced TRPM2 activation by increase of ADP-ribose production through poly(ADP-ribose) polymerase pathway. Similarly, pretreatment with FeSO4 stimulated H2 O2 -induced TRPM2 activation at 37 °C in U937 cells and enhanced H2 O2 -induced ERK phosphorylation and interleukin-8 (CXCL8) production. Although the addition of H2 O2 to cells under conditions of intracellular Fe 2+ -accumulation caused cell death, concentration of H2 O2 required for CXCL8 production was lower than that resulting in cell death. These results indicate that intracellular Fe 2+ -accumulation sensitizes TRPM2 channels to H2 O2 and subsequently produces CXCL8 at around body temperature. It is possible that sensitization of H2 O2 -induced TRPM2 channels by Fe 2+ may implicated in hemorrhagic brain injury via aggravation of inflammation, since Fe 2+ is released by heme degradation under intracerebral hemorrhage.